Glial TDP-43 regulates axon wrapping, GluRIIA clustering and fly motility by autonomous and non-autonomous mechanisms. - Romano, G.; Appocher, C.; Scorzeto, M.; Klima, R.; Baralle, F.E.; Megighian, A.; Feiguin, F. (Human Molecular Genetics, 2015)
Alterations in the glial function of TDP-43 are becoming increasingly associated with the neurological symptoms observed in Amyotrophic Lateral Sclerosis (ALS), however, the physiological role of this protein in the glia or the mechanisms that may lead to neurodegeneration are unknown. To address these issues, we modulated the expression levels of TDP-43 in the Drosophila glia and found that the protein was required to regulate the subcellular wrapping of motoneuron axons, promote synaptic growth and the formation of glutamate receptor clusters at the neuromuscular junctions. Interestingly, we determined that the glutamate transporter EAAT1 mediated the regulatory functions of TDP-43 in the glia and demonstrated that genetic or pharmacological compensations of EAAT1 activity were sufficient to modulate glutamate receptor clustering and locomotive behaviors in flies. The data uncovers autonomous and non-autonomous functions of TDP-43 in the glia and suggests new experimentally based therapeutic strategies in ALS.